The Relevance of Modern Diagnosis and Treatment of Gastrointestinal Functional Dyspepsia in Type 2 Diabetes Mellitus - Abdusattarov A.A. (Scholars Digest Publishing, 2023)
Assessment of the prevalence and study of clinical manifestations of dyspepsia syndrome and factors associated with its occurrence in patients with type 2 diabetes mellitus (DM). 107 patients with type 2 diabetes and 33 patients with functional dyspepsia were examined. A clinical and laboratory study was conducted, testing to identify symptoms of dyspepsia, and the study of factors associated with dyspepsia. Dyspepsia syndrome in patients with type 2 diabetes, which cannot be explained by gastrointestinal diseases, was associated with the duration of carbohydrate metabolism disorders, the presence of complications of diabetes, helicobacter infection and the age of patients. Some manifestations of dyspepsia syndrome (a symptom of overflow and discomfort in the epigastrium), which cannot be explained in patients with type 2 diabetes by organic gastrointestinal diseases, were associated with complications of diabetes and indicators of carbohydrate metabolism.
Keywords: dyspepsia syndrome, type 2 diabetes mellitus, Helicobacter pylori.